Endothelial Progenitor Cells Enhance Islet Engraftment, Influence β-Cell Function, and Modulate Islet Connexin 36 Expression. Issue 1 (January 2015) - Penko, Daniella; Rojas-Canales, Darling; Mohanasundaram, Daisy; Peiris, Heshan S.; Sun, Wai Y.; Drogemuller, Christopher J.; Keating, Damien J.; Coates, P. Toby H.; Bonder, Claudine S.; Jessup, Claire F.
The success of pancreatic islet transplantation is limited by delayed engraftment and suboptimal function in the longer term. Endothelial progenitor cells (EPCs) represent a potential cellular therapy that may improve the engraftment of transplanted pancreatic islets. In addition, EPCs may directly affect the function of pancreatic β-cells. The objective of this study was to examine the ability of EPCs to enhance pancreatic islet transplantation in a murine syngeneic marginal mass transplant model and to examine the mechanisms through which this occurs. We found that cotransplanted EPCs improved the cure rate and initial glycemic control of transplanted islets. Gene expression data indicate that EPCs, or their soluble products, modulate the expression of the β-cell surface molecule connexin 36 and affect glucose-stimulated insulin release in vitro. In conclusion, EPCs are a promising candidate for improving outcomes in islet transplantation, and their mechanisms of action warrant further study.